Swertia muliensis (Gentianaceae), a new species from Sichuan, China - Yu, Qi; Jiang, Li-Sha; Lin, Hong-Qiang; Zhong-Yang, Ci-Er; Xiong, Xian-Hua; Xu, Bo (Phytotaxa, 2025)
Swertia muliensis, a new species from Sichuan Province, China, is described and illustrated. It is morphologically similar to S. binchuanensis and S. mussotii, but differs in having yellow-green corolla, oblong-oval nectary, larger nectary-to-petal width ratio, capitate stigma lobes, and raised margin of the nectary towards the base of the petal with relatively longer fimbriae, and with the remainder bearing fewer and shorter fimbriae. Information of this new species including its distribution, habitat, phenology and etymology is also provided.